The bioefficacy of flavokawain C against colon cancer and the underlying mechanistic insights / Phang Chung Weng - Phang, Chung Weng (2017)
In the present study, flavokawain C, a natural-occuring chalcones, showed higher cytotoxic activity against HCT 116 cells in comparison to other cell lines tested and minimal toxicity on normal colon cell line (CCD-18Co). Cytotoxic activity of FKC was found to be caused by the activation of intrinsic, extrinsic and endoplasmic reticulum stress-mediated apoptotic pathways.This was associated with an increase in reactive oxygen species and a decrease in SOD activity. A sustained ERK1/2 activation and inactivation of PI3K/Akt were also observed. Cell cycle was found to be arrested at S phase and G2/M in HCT 116 and HT-29 cells, respectively after FKC treatment. Down-regulation of Cdk2 and Cdk4, up-regulation of p53, p21Cip1 and p27Kip1, and hypophosphorylation of pRb were observed. Proteomic analysis identified 35 proteins that changed in abundance (17 increased and 18 decreased). These proteins were found to be involved in cell death and survival, cellular growth and proliferation, cell cycle, protein synthesis, post-translational modification and amino acid metabolism. In in vivo study, FKC treatment inhibited HCT 116 tumor growth with no obvious toxicity. Induction of apoptosis and reduction in cell proliferation were shown in FKC-treated tumors. Five differentially abundant proteins from serum were also identified via proteomic analysis which can be used as potential biomarkers. Thus FKC holds great promise for use in molecular target-based chemopreventive and chemotherapeutic strategies.